Iodine content development in raw cow's milk in three regions of the Czech Republic between the years 2008 and 2018 - Konečný, Roman; Křížová, Zuzana; Hladký, Jan; Kautská, Jitka; Hasoňová, Lucie; Samková, Eva; Šimák Líbalová, Kristýna; Trávníček, Jan (Acta veterinaria Brno, 2019)
The study examines an analysis and evaluation of iodine content in raw cow's milk in three regions of the Czech Republic between the years 2008 and 2018. Bulk milk samples were collected at dairy farms situated in South Bohemia, Central Bohemia, and the Vysočina Region. Iodine in milk was determined on the basis of alkaline ashing, using the spectrophotometric method according to Sandell-Kolthoff. The highest mean iodine content was measured in 2009 (485.5 ± 408.2 μg/l) and the lowest in 2016 (169.2 ± 71.7 μg/l). Since 2010 there has been a gradual decline of iodine concentration, from 479.5 ± 304.9 μg/l in 2010 to 231.2 ± 63.5 μg/l in 2018. A similar decreasing tendency was recorded in all the monitored regions. The percentage of samples containing iodine above 500 μg/l was on the decrease (37% in 2009; 0% in 2016–2018) and less than 80 μg/l (8% in 2009; 0% in 2017–2018). The current state corresponds to the requirements for iodine content in milk for human consumption. The study emphasizes the importance of continuous iodine content checks in milk and the related adjustments of iodine supplementation to the feeding rations of dairy cows.
Keywords: Iodine; Česká republika; Food Analysis; nutriční hodnota; jod; mléko; analýza potravin; Nutritive Value; Czech Republic; Milk